Implementation of Google Classroom as Multimedia Learning - Anderias Henukh; Haris Rosdianto; Sayaka Oikawa (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
This research was carried out at Musamus University in academic year 2019/2020 by taking a basic physics class I as a research sample. The purpose of this research is to determine the effectiveness of the implementation of Google classroom as multimedia learning. The research method used in this research is descriptive qualitative supported by quantitative data. The instrument used was a material and multimedia expert validation sheet, questions that had been validated to test the effectiveness of implementing Google classroom as learning multimedia. Based on the description above it can be concluded that the implementation of google classroom as multimedia learning with average results of multimedia expert validation of 82.5% and 87% of material experts have a good impact on the learning process and outcomes of students. This is evidenced by an increase in the value of each student with average of pre-test score is 62 and post-test score is 83. N-gain score is 0.75 (high category).